2002
DOI: 10.1038/oby.2002.95
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Changes in Fatty Acids in Obese Offspring of Streptozotocin‐Induced Diabetic Rats

Abstract: MERZOUK, HAFIDA, SIHEM MADANI, AZIZ HICHAMI, JOSIANE PROST, JACQUES BELLEVILLE, AND NAIM A. KHAN. Age-related changes in fatty acids in obese offspring of streptozotocin-induced diabetic rats. Obes Res. 2002;10:703-714. Objective: The long-term effects of fetal hyperinsulinemia, time course of changes in liver and very-low-density lipoprotein (VLDL) lipid levels and fatty acid compositions were investigated in obese offspring of streptozotocin-induced mildly diabetic rats. Research Methods and Procedures: Mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
2
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(78 citation statements)
references
References 48 publications
(97 reference statements)
6
66
2
4
Order By: Relevance
“…42,43 Maternal diabetes mellitus also induced hypercholesterolemia and hypertriglyceridemia in obese offspring, and this observation corroborated our previous studies. 22,24,39 In the present study, we observed a high level of cholesterol in the offspring of the control group at day 60; however, this level remained significantly lower than that of macrosomic offspring. In fact, a significant age-related change in serum cholesterol concentration has been evoked, 44 and this can be explained by the existence of a compensatory mechanism for maintenance of hepatic cholesterol homeostasis with age.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…42,43 Maternal diabetes mellitus also induced hypercholesterolemia and hypertriglyceridemia in obese offspring, and this observation corroborated our previous studies. 22,24,39 In the present study, we observed a high level of cholesterol in the offspring of the control group at day 60; however, this level remained significantly lower than that of macrosomic offspring. In fact, a significant age-related change in serum cholesterol concentration has been evoked, 44 and this can be explained by the existence of a compensatory mechanism for maintenance of hepatic cholesterol homeostasis with age.…”
Section: Discussionmentioning
confidence: 56%
“…22 Feeding the n-3 PUFA diet significantly reduced the incidence of gestational diabetes on macrosomia by decreasing the rate of macrosomic pups at birth from 64 to 48%. However, n-3 PUFA diet had no effect on hyperglycemia of macrosomic offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La surproduction de VLDL, une caractéristique commune à l'obésité humaine et aux différentes obésités expérimentales, a été une conséquence directe de l'hyperinsulinémie et de l'hyperlipogenèse hépatique (Bioletto et al, 2000). La première observation importante apparente à l'âge de 3 mois, c'est-à-dire à l'âge adulte, est que ces rats avaient pris progressivement du poids et leur gain pondéral a été significativement plus élevé que celui des rats contrôles (Merzouk et al, 2002). En outre, ils ont été hyperglycémiques et hyperinsulinémiques, avec des concentrations élevées en lipide et lipoprotéine.…”
Section: Le Métabolisme Des Lipides Et Des Lipoprotéines Est Altéré Cunclassified
“…En fait, cette programmation in utero semble créer une sorte de ''mémoire métabolique'' puisque les anomalies observées dans le système physiologique pendant la période gestationnelle sont responsables, à l'âge adulte, de ''l'apparition'' de maladies comme le diabète de type 2 et l'obésité, associées au syndrome métabolique. Il existe, chez la mère et le foetus âgé de 6 mois, une bonne corrélation entre les taux plasmatiques en cholestérol et, certaines altérations telles que les taux élevés de triacylglycérol (TAG), apoB100, VLDL, LDL ont souvent persisté chez les nouveau-nés macrosomiques après un mois de vie (Merzouk et al, 2002). Nous avons montré, chez les rats macrosomiques nés de mères GDM, que la plupart des paramètres lipidiques se sont normalisés vers l'âge de 2 mois et ont réapparu à l'âge adulte.…”
Section: La Programmation In Utero Semble êTre Responsable Des Modifiunclassified